A preliminary study of 'dukung anak' (phyllanhus nirurilinn) plant extracts on haema to logical parameters - Mohamed, Norayuni (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
The aim of this study was to assess the effect of 'dukung anak' plant (Phyllanthus niruri Linn) on human blood particularly on mean platelet volume (MPV) based on in vitro experiment. The effect of the plant extracts were studied based on observation and analysis of changes in mean platelet volume (MPV) and other blood parameters like haemoglobin within two hours following treatment with 'dukung anak' plant extracts. The blood parameters analyses were done on automated haematology analyzer (Abbott Cell Dyn. Model: 4000). Three doses of water and ethanol extracts of'dukung anak' plant were used to determine their effect on blood MPV in order to assess the ability of the extracts to prevent platelet aggregation. 'Dukung anak' plants were harvested around Pasir Tumboh area of Kelantan. Subsequently all parts of 'dukung anak' plants were dried and extracted by organic and non-organic solvents. The organic solvent used was ethanol, while non-organic was distilled water. The extracts were dried into powdered form. From the powdered extract obtained, calculation of three dosages of each type of extract was done based on the amount of extract powder, volume of solvent and amount of blood to be used for testing. The extract was then dissolved in phosphate buffer saline (PBS) of pH 7.3 to form an extract solution. The extract solutions obtained were tested on five fresh human bloods from different healthy donors. The effect of extracts on blood were studied at 0 minute to 120 minutes following treatment with the intervals of every half an hour at 30 minutes, 60 minutes, 90 minutes and 120 minutes respectively. In the entire research, the dosage of extracts used were at O.OOlmg, O.Olmg and 0.1mg of extracts per 1 milliliter (ml) of blood and the tests were done within 2 hours following treatment with the extracts. The data obtained were then analyzed with the SPSS program version 11.5 for Windows. The results of this study showed that O.lmg of ethanol extract of the 'dukung anak' plant for evecy 1 ml blood did not give any significance changes on mean platelet volume (MPV). The result also showed that the all three doses of the water and ethanol extracts of 'dukung anak' plant did not cause any changes on haemoglobin value. This observation means that the 'dukung anak' plant did not cause any negative side effects on the blood parameters. Based on these preliminary findings the initial hypothesis that the 'dukung anak' plant extracts were able to prevent significance changes on MPV and hence preventing platelets activation with no side effect on blood were substantiated. However this result should be confirmed with more extensive studies on animals (in vivo studies) based on platelet activities using a specific instrument such as platelet function analyzer or platelet aggregometer. For control, all the three doses of water extracts of 'dukung anak:' plant (O.OOlmg, O.Olmg, O.lmg), O.OOlmg and 0.01mg ethanol extracts of 'dukung anak' plant for evecy 1 milliliter of blood following treatment were shown to have some significance changes on MPV.